2019
DOI: 10.1111/lam.13104
|View full text |Cite
|
Sign up to set email alerts
|

Fibre degradation of wheat straw by Pleurotus erygnii under low moisture conditions during solid-state fermentation

Abstract: The application of solid‐state fermentation offers an alternative to conventional, submerged approaches for a variety of bioconversion processes, including animal feeds, biofuels and fungal bioproducts. Optimizing solid‐state fermentation under low moisture conditions could significantly impact the proportion of dry biomass that could be processed and improve the commercial viability of this approach, because of reduced input costs and higher yields of final products. Pleurotus erygnii that appeared to show to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Figure 2 depicts the time evolution of the morphological aspect of wheat straw treated in both reactor configurations. It is observed that wheat straw is a suitable feedstock for WRF, as previously reported [35,36]. However, when comparing the wheat straw colonisation on day 4, it is evident that I. lacteus grew faster in the packed bed configuration.…”
Section: Operation and Monitoring Of The Ssf Bioreactorsupporting
confidence: 69%
“…Figure 2 depicts the time evolution of the morphological aspect of wheat straw treated in both reactor configurations. It is observed that wheat straw is a suitable feedstock for WRF, as previously reported [35,36]. However, when comparing the wheat straw colonisation on day 4, it is evident that I. lacteus grew faster in the packed bed configuration.…”
Section: Operation and Monitoring Of The Ssf Bioreactorsupporting
confidence: 69%
“…and their allies belong to the complex. Because of its nutritional and medical properties, as well as diverse biotechnological applications, the P. ostreatus species complex is one of the three most actively cultivated mushroom species in the world (Baker et al 2018;Cardwell et al 2018;Golak-Siwulska et al 2018). As commonly found saprotrophic mushrooms, species within the P. ostreatus complex constitute essential components in forest and grassland ecosystems because of their roles as decomposers of a large array of lignocellulosic substrates, such as deciduous trees (Kay and Vilgalys 1992;Petersen and Krisai-Greilhuber 1996), coniferous trees (Petersen and Hughes 1997;Vilgalys et al 1993), as well as herbs in the Apiaceae family (Zervakis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…was 33% [26]. These values are considerably lower than the atypical low moisture content of 67%, which only supported the growth of only one species of white rot fungi, Pleurotus erygnii, on wheat straw [27]. This study also reported that the addition of 30% wheat bran to wheat straw reduced the moisture content to 44%, but this level of moisture continued to support the growth of P. erygnii.…”
Section: Growth Of T Versicolor On Wheat Bran Over Timementioning
confidence: 57%